2021
DOI: 10.1093/femsre/fuab007
|View full text |Cite
|
Sign up to set email alerts
|

Verrucomicrobial methanotrophs: ecophysiology of metabolically versatile acidophiles

Abstract: Methanotrophs are an important group of microorganisms that counteract methane emissions to the atmosphere. Methane-oxidising bacteria of the Alpha- and Gammaproteobacteria have been studied for over a century, while methanotrophs of the phylum Verrucomicrobia are a more recent discovery. Verrucomicrobial methanotrophs are extremophiles that live in very acidic geothermal ecosystems. Currently, more than a dozen strains have been isolated, belonging to the genera Methylacidiphilum and Methylacidimicrobium. Ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
99
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 60 publications
(102 citation statements)
references
References 246 publications
3
99
0
Order By: Relevance
“…One single pmoCAB operon and a pmoD subunit, encoding a copper-binding protein ( Fisher et al, 2018 ), were found in MAG9, whereas no other mmo genes were identified ( Table 3 ). This is in line with previously described verrucomicrobial methanotrophs, although the number of pmo operons seems to be variable ( Op den Camp et al, 2009 ; van Teeseling et al, 2014 ; Erikstad et al, 2019 ; Picone et al, 2020 ; Schmitz et al, 2021 ). The PmoA phylogenetic tree including strain PQ17 ( Supplementary Figure 3 ) supports the phylogeny derived from 16S rRNA gene analysis.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…One single pmoCAB operon and a pmoD subunit, encoding a copper-binding protein ( Fisher et al, 2018 ), were found in MAG9, whereas no other mmo genes were identified ( Table 3 ). This is in line with previously described verrucomicrobial methanotrophs, although the number of pmo operons seems to be variable ( Op den Camp et al, 2009 ; van Teeseling et al, 2014 ; Erikstad et al, 2019 ; Picone et al, 2020 ; Schmitz et al, 2021 ). The PmoA phylogenetic tree including strain PQ17 ( Supplementary Figure 3 ) supports the phylogeny derived from 16S rRNA gene analysis.…”
Section: Resultssupporting
confidence: 92%
“…Phylogenetic analysis showed that the 16S rRNA gene of MAG9 clustered in between Methylacidimicrobium and Methylacidiphilum species ( Figure 1 ; Dunfield et al, 2007 ; Pol et al, 2007 ; Op den Camp et al, 2009 ; van Teeseling et al, 2014 ; Schmitz et al, 2021 ). The 16S rRNA and AAI values ( Table 1 and Supplementary Table 1 ) fell below the threshold for species delimitation (95% for AAI and 98.7–99% for 16S rRNA) ( Stackebrandt and Ebers, 2006 ; Thompson et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations